Meaning of life karyawan penderita kanker (FENOMENA, 2021)
This study aims to find out more about the meaning of life of individual employees in the company who have been sentenced to cancer. Cancer comes from the Greek word karkinos, which means coral, which is a general term for hundreds of different malignant tumors. Cancer is also a term used for diseases in which abnormal cells divide without control and are able to invade other tissues. This research is qualitative research using phenomenological methods. The results of this study say that the meaning of life in this study has something to do with work motivation. Participant's work motivation is to fulfill Maslow's hierarchy of needs. Besides that, it also works as a coping strategy for participants so that they are not stressed about the disease they are suffering from, this is called emotion focused coping. This is what makes the participants keep working even though they have terminal cancer.